Pengaruh Pemberian Latihan Olah Vokal Terhadap Kebutuhan Tidur Lansia Dengan Metode Pendekatan Asuhan Keperawatan Gerontik - Cahyo Prasetyo Rifianto (2014)
Fulfillment adequacy of sleep disorders is influenced by several factors such as mental, psychological, degeneration process, activity, and environment. One of the alternative therapies used is vocal exercises. Vocal exercises 3 times a week can stimulate the baroreceptors to produce oxygen and circulated throughout the body so that it can be formed hormone endorphin and generate a sense of comfort and relaxation. The purpose of this study was to analyze the effect of vocal training on the adequacy of sleep quality and quantity based on the fulfillment of the elderly (and sleep time vital sign: blood preassure and pulse). This study was used Pra Experiment design with one group pre-post test design. The population were elderly at Karang Werdha Bismo Madiun, 25 respondents taken by purposive sampling technique an 23 respondents were include. Variable independent in this research is vocal training and variable dependen in this research is vital sign. Vocal training was done by respondent during three weeks at 05.30-06.00 am, three times a week. Data were collected by using PSQI and Vital Sign . Data were analyzed using the wilcoxon sign rank test to fulfillment adequacy of sleep on quality, quantity of sleep was measured using the measurement of blood pressure and pulse Paired t-test to fulfillment adequacy of sleep on quantity with significance α0,05. The results of the data analysis showed an increase in compliance adequacy elderly sleep after doing vocal for 3 weeks. Fulfillment sleep adequacy based on quality shows that p=0.000. Sleep adequacy based on the quantity of shows that p=0.008 in systole, sleep duration p=0.002. It can be conclude that vocal exercise for 3 times a week can improve sleep adequacy of compliance in the elderly based on the quality and quantity. Nurses or health volunteer in this district can continue this activity to improve the quality of sleep in elderly. Further measurements have to measure the effect of vocal training onthe adequacy of compliance with melatonin levels.